Examining the UTAUT Framework in Understanding the Perception-Intention Dynamics of Accounting Information Systems in the Age of Industry 4.0 - Asrori Asrori; Muhammad Ihlasul Amal (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: This research investigates the relationship between students' perceptions of a digital accounting laboratory and their intention to utilize it. This research is conducted in response to the challenges and opportunities posed by the Fourth Industrial Revolution and the Digital Economy.Method: The study adopts the Unified Theory of Acceptance and Use of Technology (UTAUT) to understand and explain the factors influencing students' intention to use the Digital Accounting Laboratory. Data were collected from students in the Department of Accounting at the Faculty of Economics and analyzed using SEM-PLS statistical method.Findings: The research findings indicate that students' intention to utilize the Digital Accounting Laboratory for project-based learning, to enhance their competency in digital accounting during the era of the Industrial Revolution 4.0 and the Digital Economy is significantly high. The intention is positively influenced by performance expectations, effort expectancy, social influences, and facilitating conditions. Furthermore, the use of Digital Accounting Laboratories contributes to improving students' competence in digital accounting, aligning with the needs of business entities in the Industrial Revolution 4.0 era and the Digital Economy.Novelty: This research contributes to the field by providing insights into developing and utilizing digital technologies in accounting education. Establishing a Digital Accounting Laboratory and its positive impact on students' intention and competence in digital accounting offer new perspectives for adapting to the challenges and opportunities of the Industrial Revolution 4.0 and the Digital Economy.